Engenho teatral: apontamentos sobre determinadas relações entre teatro e sociedade - Resende, Fábio [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Em 1979, surge, na cidade de São Paulo, o Grupo Apoena, que, a partir de 1986, junta-se ao Grupo Engenho de Artes e passa a se chamar Engenho Teatral. Eram dois grupos que se juntaram depois de uma experiência prática comum e marcados pela mesma insatisfação com as limitações da produção teatral profissional de São Paulo e de sua época: a falta de condições materiais; a relação com o público totalmente distante, formal e comercial; e as limitações impostas pela ditadura civil- militar. Essa insatisfação fez com que o Engenho Teatral abandonasse o circuito tradicional do teatro paulistano, conhecido como “circuito do Bixiga”, e fosse em busca de outro público: a classe trabalhadora. Por meio desta pesquisa, apresento apontamentos sobre a relação entre teatro e sociedade a partir da história de mais de 40 anos do Grupo Engenho Teatral. Tais apontamentos são apresentados por meio de três fases do Grupo: 1979 a 1990; 1991 a 2002; e de 2003 até a estreia da peça Canção Indigesta.

In 1979, the theater group Apoena rises in the city of São Paulo and then, in 1986, as it merges with another theater group, the Engenho de Artes, is born the Engenho Teatral. The first two groups came together after a journey of practical common experience and they bonded over the same dissatisfactions with the limitations of professional theatrical production of the time and specifically in the city area: a lack of material conditions; a completely distanced, formal and commercial relationship established with the audiences; and the limitations imposed by the running civil-military dictatorship. Such dissatisfactions led Engenho Teatral to abandon the traditional theatrical circuit of São Paulo, also known as the “Bixiga circuit”, in search of a different audience: the working class. Along this research, I present notes on the relationship between theater and society while recovering the history of more than 40 years of the Engenho Teatral Theater Group. The presented historical trajectory is divided into three stages: 1979 to 1990; 1991 to 2002; and 2003 until the premiere of the play Canção Indigesta (Indigestible Song).
Engenho teatral: notes on certain relationships between theatre and society
Keywords: Teatro; Teatro de grupo; Teatro épico; Engenho teatral; Theater; Group theater; Epic theater